Isu Syiah Sesat di Universitas Islam Negeri Raden Fatah Palembang; Studi Atas Pandangan Akademisi Dalam Upaya Deradikalisasi Faham Keagamaan - Noupal, Muhammad (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
The background to this article is due to the issue of heretical sects against Shia teachings in the view of lecturers or academics at Islamic Religious Colleges (PTKI), including at Raden Fatah State Islamic University (UIN) Palembang. It is feared that the issue of heretical sects will lead to intolerance and radical thinking, such as making statements